Maximin Paths of Heterogeneous Capital Accumulation and the Instability of Paradoxical Steady States - Burmeister, E.; Hammond, P. J. (Econometrica, 1977)
If there exist heterogeneous capital goods, a steady state may be "paradoxical" in the sense that increasing the rate of interest above the Golden Rule level may lead to an increase in consumption or utility, rather than to the decrease which always occurs in one-sector models. It is shown that, in many cases, a path of capital accumulation which maximizes the minimum consumption or utility level is unlikely to converge to a paradoxi- cal steady state of this kind.